TOWARDS UNDERSTANDING THE ISLAMIC CONCEPT OF THE HEART AND ITS RELATIONSHIP WITH MAN’S INTENTION/ACTIONS - Olatoye, Raji Mubin (European Scientific Journal, ESJ, 2013)
In Islam the heart is viewed as the essence of man. This is due to the fact that it t occupies a great and lofty position in the spiritual development of man; the place to which God looks and the storehouse for tawhid, faith and sincerity. In actual fact, actions in Islam are distinguished with respect to their excellence in the sight of Allah in accordance with the condition of the heart. In spite of its lofty position, it was discovered that Muslims, especially in the contemporary period have lost the understanding of the importance of the role of the heart. Their focus is generally on actions or beliefs with little regards for the intention. It is in the light of the above that this paper attempts to increase Muslims’ understanding on the role of the heart in the psychological and development of man, and also to emphasize the relationship that exists between it and intention/actions of man. This has been carried out from the Islamic perspective using the Qur’an and sunnah as framework.